2013
DOI: 10.7554/elife.00603
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary principles of modular gene regulation in yeasts

Abstract: Divergence in gene regulation can play a major role in evolution. Here, we used a phylogenetic framework to measure mRNA profiles in 15 yeast species from the phylum Ascomycota and reconstruct the evolution of their modular regulatory programs along a time course of growth on glucose over 300 million years. We found that modules have diverged proportionally to phylogenetic distance, with prominent changes in gene regulation accompanying changes in lifestyle and ploidy, especially in carbon metabolism. Paralogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 72 publications
6
125
1
Order By: Relevance
“…The contribution of paralogs resulting from WGD to regulatory divergence is more pronounced and longer lasting than the contribution of genes arising through small-scale duplications [25 ]. This regulatory divergence can drive regulatory network evolution and rewiring and lead to regulatory innovation [26 ,27,28].…”
Section: Main Text Of Reviewmentioning
confidence: 99%
“…The contribution of paralogs resulting from WGD to regulatory divergence is more pronounced and longer lasting than the contribution of genes arising through small-scale duplications [25 ]. This regulatory divergence can drive regulatory network evolution and rewiring and lead to regulatory innovation [26 ,27,28].…”
Section: Main Text Of Reviewmentioning
confidence: 99%
“…Cells were cold methanol quenched exactly as described in Thompson et al (2013) right before the addition of 5 mM H 2 O 2 or 5 and 15 min post H 2 O 2 addition. Hydrogen peroxide is a suitable proxy for host response as it is the most common ROS used by the immune system during respiratory burst (Iles and Forman 2002), and passes through the cell membrane, reaching the cytoplasm quickly (Kohchi et al 2009).…”
Section: Expression Profilingmentioning
confidence: 99%
“…It was previously reported that duplicate genes evolve rapidly in expression pattern (Li et al 2005;Thompson et al 2013). If the inferred neofunctionalization after gene duplication is attributable to gains of new expression patterns, duplicates with fitness gains are expected to have larger expression differences and smaller expression correlations across cell cycle stages or media compared with those without fitness gains.…”
Section: Gains Of Protein-protein Interactions Could Explain the Neofmentioning
confidence: 99%